2007
DOI: 10.1589/rika.22.547
|View full text |Cite
|
Sign up to set email alerts
|

Current State and the Future of E-learning in Physical Therapy Education

Abstract: The use of the internet in medical education is expanding along with the progress of IT Technology. In the midst of drastic changes in education strategy and methods of learning, we review what e-learning is, aspects of it and its history, as well as present controversial topics and the actual situation of its use in a medical education. Furthermore, we review how we should utilize e-learning in physical therapy education in the future and what we should aspire to do with it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is true also for other health professionals’ education, but in terms of e‐learning used in higher education, Japan is reportedly behind some other countries (11–13). Admittedly, some infrastructure problems exist in technical schools and junior colleges (12–14).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is true also for other health professionals’ education, but in terms of e‐learning used in higher education, Japan is reportedly behind some other countries (11–13). Admittedly, some infrastructure problems exist in technical schools and junior colleges (12–14).…”
Section: Introductionmentioning
confidence: 88%
“…Rosenberg et al (10) found that computer-aided learning elicited a positive response from students and motivated students to learn. This is true also for other health professionals' education, but in terms of e-learning used in higher education, Japan is reportedly behind some other countries (11)(12)(13). Admittedly, some infrastructure problems exist in technical schools and junior colleges (12)(13)(14).…”
Section: Introductionmentioning
confidence: 97%
“…This is true also for medical education, but in terms of e-learning used in higher education, Japan is reportedly far behind other countries such as European countries, the US, and Korea 1) .…”
Section: Introductionmentioning
confidence: 99%